2016
DOI: 10.1590/0100-3984.2015.0002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of the morphometric patterns of lymph nodes of the head and neck in young and middle-aged individuals

Abstract: ObjectiveTo show the morphometric patterns of lymph nodes of the head and neck, evaluating their number, shape, dimensions, hilum, and cortex, through the use of ultrasound examination of the neck.Materials and MethodsWe analyzed 400 right and left lymph nodes in a group of 20 healthy young and middle-aged individuals of both genders.ResultsIn the ultrasound examination, we observed the following lymph nodes: mastoid; parotid (superficial, extraglandular, and intraglandular); submandibular (preglandular, retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
2
4
0
3
Order By: Relevance
“…In our study, the LNs with malignant cytology were mostly oval, as well as benign LNs. Th e majority of rounded and irregularly shaped LNs were malignant by FNAC, an observation consistent with the previously reported studies 8,[23][24][25] . Nevertheless, it has been reported that normal submandibular and parotid nodes, as well as the LNs related to some non-malignant diseases such as tuberculosis 7 , are often round 26,27 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the LNs with malignant cytology were mostly oval, as well as benign LNs. Th e majority of rounded and irregularly shaped LNs were malignant by FNAC, an observation consistent with the previously reported studies 8,[23][24][25] . Nevertheless, it has been reported that normal submandibular and parotid nodes, as well as the LNs related to some non-malignant diseases such as tuberculosis 7 , are often round 26,27 .…”
Section: Discussionsupporting
confidence: 91%
“…Nesse contexto, devido à íntima relação dessas estruturas com o sistema imune, o conhecimento anatômico e morfológico dos linfonodos cervicais são fundamentais para o reconhecimento de diversas patologias com comprometimento local, tais como linfomas, tuberculose e metástases tumorais. Entretanto, não são todos os linfonodos que serão palpáveis durante o exame físico, sendo os métodos de imagem essenciais para o auxílio diagnóstico (OGASSAVARA et al, 2016).…”
Section: Introductionunclassified
“…Mastoid lymph nodes (MLNs), or retroauricular lymph nodes 1 , are a small group of usually two nodes that belong to the superficial lymph node group of the head 2 . They are located in both retroauricular areas, in the mastoid region and are more numerous in children 3 .…”
Section: Introductionmentioning
confidence: 99%